2017
DOI: 10.1007/s12032-017-0953-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of biomarkers and their functions for Lapatinib-resistant breast cancer

Abstract: Lapatinib, a novel oral dual tyrosine kinase inhibitor blocking HER1 and HER2 pathways, has presented beneficial effects on breast cancer with positive HER2. However, its efficacy is largely limited by the occurrence of acquired drug resistance. In this study, we aimed to explore the underlying molecular mechanisms of Lapatinib resistance using bioinformatics strategies. The gene expression profile of SKBR3-R (acquired Lapatinib-resistant) and SKBR3 (Lapatinib-sensitive) cell line was downloaded from gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…However, a microarray-based gene expression analysis identified high expression of TGFBI involved in topotecan-resistant ovarian cancer [252]. Moreover, it has been reported that TGFBI might be associated with Lapatinib resistance in HER2-positive breast cancer cell lines [253]. On the other hand, epigenetic silencing of TGFBI by DNA methylation has been found to contribute to the trastuzumab resistance in HER2-positive cell models [254].…”
Section: Transforming Growth Factor B Induced (Tgfbi) Protein and Brmentioning
confidence: 99%
“…However, a microarray-based gene expression analysis identified high expression of TGFBI involved in topotecan-resistant ovarian cancer [252]. Moreover, it has been reported that TGFBI might be associated with Lapatinib resistance in HER2-positive breast cancer cell lines [253]. On the other hand, epigenetic silencing of TGFBI by DNA methylation has been found to contribute to the trastuzumab resistance in HER2-positive cell models [254].…”
Section: Transforming Growth Factor B Induced (Tgfbi) Protein and Brmentioning
confidence: 99%
“…The GO is a structured and controlled vocabulary of terms, and widely recognized as the premier tool for the organization and functional annotation of molecular characteristics [18,20,21]. By interpreting the GO of differentially expressed proteins and then analyzing them statistically, we have obtained 42 significant CSF proteins and 57 significant plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The screening criteria were adjusted P < 0.001 (Z. Lin & Lin, 2017;L. Zhang et al, 2017) and |fold change | ≥ 1.5.…”
Section: Identification Of Degsmentioning
confidence: 99%